The impact of environmental regulations on innovation in heavy polluting enterprises: a quasi-natural experiment based on environmental tax reform - Chen, Yao; Pei, Yuhao; Wang, Jianlin (Frontiers in Environmental Science, 2026)
This paper uses data from the CSMAR database and listed companies’ annual reports to examine the impact of China’s 2018 environmental tax reform on the innovation capacity of heavily polluting enterprises. Treating the policy as a quasi-natural experiment, the study finds that the reform significantly enhances innovation in such firms, with results remaining robust across various tests. Heterogeneity analysis reveals that the policy’s positive effect is stronger in state-owned, large-scale, and high-tech heavy polluters compared to their counterparts. Furthermore, the mechanism analysis reveals that the reform primarily promotes innovation by increasing R&D investment. Further analysis shows that the environmental tax reform also enhances firms’ innovation quality and efficiency, and exerts a significant impact on both green and non-green innovation. These findings offer policy implications for leveraging environmental regulations to foster green innovation in polluting industries.